La nourriture dans le monde francophone - Diack, Fatou (Kansas State University, 2010)
This report is a portfolio demonstrating my background and commitment to teaching. It contains a collection of activities that I have created that demonstrates that students learn better when they are exposed to authentic input, provided through interaction. These activities are based on the theories of the Zone of Proximal Development (ZPD) as conceptualized by Lev SemyonovichVygotsky. ZPD is based on what a learner can or cannot do with the help of a more proficient speaker. This theory affirms that language acquisition is greatly facilitated by the use of the target language in interaction. The pedagogical unit contained in this report is designed to teach college-aged native English speakers (English L1) learning French as a Second Language. Thus, they are learning French while living in a Francophone country. The teacher should be fluent in both French and English. This unit is designed to be taught in the middle of a four-month semester of an elementary French class. It should be the fifth out of ten lessons that constitute a whole semester. It is designed to build upon the four previous lessons taught. The objectives of this unit are to familiarize students with food-related vocabulary and grammar. Comparisons and contrasts between their L1 and L2 cultures will be made whenever necessary. Students will be encouraged to raise critical questions about their culture and the new cultural elements that are being taught. I incorporated the four skills that are reading, writing, speaking, and listening in the lessons I designed. I have also taken into account the different types of learners, namely the visual, audio and hands-on learners, to give all students opportunities to learn. The grammar lessons have been contextualized following the Presentation, Attention, Co-construct and Extension (PACE) model, developed by Richard Donato and Bonnie Adair-Hauck. This teaching unit is engaging and diverse as it sees French language through different perspectives. The majority of activities are cooperative and they encourage all students to participate in class. An instructor could easily teach with it following the clearly labeled teaching guides. It can also be a good source for lesson plan design.
Keywords: Nourriture; Francophone; Language, Modern (0291)